Green bonds and climate change mitigation: A conceptual study of financial instruments in India - Reddy, K. Manikanteswara; Srinivas, Ch.; Devi, P. Uma Maheswari (Goodwood Publishing, 2024)
Purpose: This study examines the potential of green bonds as essential financial instruments for mitigating climate change, with a particular focus on their development and application in India. Method: A qualitative approach was adopted, synthesizing secondary data from academic literature, case studies, and policy documents to analyze the barriers, opportunities, and regulatory frameworks influencing the green bond market in India. Results: The findings reveal that although green bonds are gaining traction, their adoption in India is hindered by challenges such as regulatory inconsistencies, information asymmetry, greenwashing risks, and market volatility. However, initiatives like Sovereign Green Bonds (SGBs), and the integration of FinTech solutions provide pathways for overcoming these barriers. Conclusions: Green bonds offer a powerful mechanism for driving sustainable finance and climate action in India. Limitations: The study is limited by the evolving nature of the green bond market and the lack of standardized definitions within India's regulatory framework. Contribution: By identifying key barriers and enabling mechanisms, this study provides actionable insights to policymakers and stakeholders to foster the growth of green bonds, aligning with India’s climate finance and sustainability goals. Novelty: The research presents a strategic framework that integrates global standards, technological innovations, and collaborative financial practices to enhance the credibility and scalability of green bonds in India.